From Brest-Litovsk via St. Germain to Sèvres - A Legal Perspective on the Peace Treaties and the Disintegration of Three Multi-ethnic Empires at the End of the First World War - Miriam Gassner (Journal on European History of Law, 2023)
The paper aims at shedding light on the initial situation of the Russian, Habsburg and Ottoman Empire at the end of the First World War and discusses the development of the Peace Treaties of Brest-Litovsk, St. Germain and Sèvres. It analyses and compares the provisions of all three peace treaties in question and tries to put them in context. As the German Reich and the Treaty of Versailles already have been subject of numerous academic studies, the paper deliberateley focuses on three before mentioned Peace Treaties, which all played a key role in the decline of multi-ethnic empires.